O exercício do controle social no âmbito de Conselhos de Assistência Social no Ceará: uma avaliação em processo - Serra, Maria Tereza de Araújo (2013)
The study circumscribes the theme “The exercise of Social Control within the Councils of Social Service: An Ongoing Evaluation”. The reasons for this investigative project have their source within the researcher’s own professional experience as a Social Worker and public servant related to the implementation of Public Policies of Social Service in the State of Ceara. The researcher’s interest fell on the investigation of Social Control related to the public administration of social service, which is one of several tools of participative administration according to the Decentralized and Participative System regulated by the Federal Constitution of 1988, and by the Organic Law of Social Service (LOAS) of 1993. It was chosen as research fields the State’s Council of Social Service and the municipal councils of Social Service of Fortaleza and Horizonte in the effort to reveal how the participative dynamics and the social control function relation to those three councils. The study consists in evaluating limits and possibilities of those public undertakings aimed at making it possible the decentralization of public policies of social service and guarantee direct control by society of governmental administration of those policies. In a very specific way it was tried by the researcher to reach the following objectives: to rescue the efforts expended in the implantation of Social Service Policies in the State of Ceara highlighting the institutionalization of Councils; to evaluate the process of society’s participation in decisions dealing with establishing Social Service Policies; to analyze the potentialities of Councils in defending social service rights within the context of re-dimensioning relations between state and society; configure action strategies adopted by the Councils within the realm of their competence. The research encompassed a bibliographic study, investigation of documents and field research. An exhaustive analysis was carried on documents issued by the Councils rescuing information and data, in this fashion reconstructing the memory related to those undertakings. Field work involved several alternatives: systematic observation of ordinary and extraordinary meetings of the three Councils under examination, evaluation of commissions and training of counselors; interviews with technicians from former LBA (Brazilian Legion of Social Assistance), SAS (Social Action Secretariat) and STDS (Labor and Social Development Secretariat); and with presidents, vice-presidents and former presidents of the Councils. In this way, it rescues the critical evaluation of technicians and counselors revealing the distance between conception and reality of councils. In concluding, the study reassesses potentialities, limits and tensions experienced within spaces of Councils in the exercise of social control according to a condition of a political process under way.